A NeutroEconomic Resilience Framework for High-Quality Regional Economic Development Under the New Normal - Yifan Wang; Xiuling Sun (Neutrosophic Sets and Systems)
This study introduces the NeutroEconomic Resilience Framework (NERF), a novel model leveraging NeutroAlgebra to enhance high-quality regional economic development under the New Normal. NERF integrates economic resilience, environmental efficiency, and social inclusivity into a composite index, using neutrosophic operations and axioms to model uncertainty. Unlike traditional models, NERF handles indeterminate and outer-defined economic interactions, offering flexibility in resource allocation and policy design. A detailed case study in Shaanxi Province, China, demonstrates a 15-20% improvement in development outcomes compared to linear optimization. The findings underscore NeutroAlgebra's potential in addressing complex economic challenges.